Amabiko: The Oceanic Ape and Its Rhizomatic Body - Castiglioni, Andrea (Journal of Religion in Japan, 2023)
The amabiko アマビコ is a chimerical aquatic hybrid similar to an oceanic ape with oracular and thaumaturgic powers, which inspired ludic and religious micro-practices in the late Edo (1603–1868) and early Meiji periods (1868–1912). The present study investigates the genealogy of the amabiko and the pivotal role played by itinerant sellers known as news criers (yomiuri) in the diffusion of images and stories concerning the amabiko, its worshiping protocols, and talismanic effects. Beyond the philological analysis of written documents, I also examine hitherto understudied prints and local gazetteers’ illustrations to understand the salvific value and “ocular luck” (ganpuku) associated with the amabiko. Moreover, this article shows how the socio-religious milieu concerning the amabiko had a trans-social nature, spanning both elite and subaltern classes. The amabiko’s physicality also provides a unique opportunity to explore the uncanny and polysemic contact areas between human and nonhuman bodies.